The Relationship Between Knowledge, Attitude, and Experience with Behaviour of Personal Protective Equipment (PPE) Use Among Fishermen - Hariyanti, Catur Oktivia; Budiono, Nugrahadi Dwi Pasca; Inayah, Zufra; Mindiharto, Sestiono (Ahmar Metastasis Health Journal, 2025)
Small-scale fishermen typically engage in fishing using traditional tools and methods, which carry a high risk of occupational accidents and work-related illnesses. This study aims to analyze the relationship between knowledge, attitude, and experience with the behaviour of personal protective equipment (PPE) use among fishermen in Tambakboyo Village, Tuban Regency. The research employed a survey design with a cross-sectional observational approach. The study population consisted of 200 rompok fishermen from Jetis Hamlet, Tambakboyo Village, Tambakboyo District, based on data provided by the local village administration. A total of 134 respondents were selected through simple random sampling. The independent variables in this study were knowledge, attitude, and experience, while the dependent variable was the behaviour of PPE application. Data collection instruments included questionnaires assessing knowledge, attitude, and experience, as well as a checklist form to evaluate PPE usage behaviour. The results showed a significant relationship between knowledge (p = 0.000 < 0.05) and attitude (p = 0.000 < 0.05) with PPE usage behaviour. However, no significant relationship was found between experience and PPE usage behaviour (p = 0.615 > 0.05). In conclusion, knowledge and attitude are associated with PPE use behaviour among fishermen, whereas experience is not. It is recommended that fishermen prioritise occupational safety and health by consistently and properly using PPE before and during fishing activities.